ELECTROLYTES, PROTEINS AND OSMOLALITY IN THE AMNIOTIC FLUID OF MICROCHIROPTERAN BAT HIPPOSIDEROS SPEORIS (SCHNEIDER) - JAYASHREE TIRPUDE (The Bioscan, 2012)
The precise origin of the liquor amnii still remains unsolved. It is probably of mixed maternal and foetal origin. In the present paper osmolality or the measures of total concentration of all dissolved solutes was studied. The biochemical estimation of electrolytes, albumin, globulin and A/G ratio were estimated except variations in chloride values not much difference was observed in all estimated values. The purpose of this study is to present some observations on certain chemical constituents of amniotic fluid at term. The mean values for electrolytes i.e. Na+ - 140.63±0.49meq/L, K+- 3.83± 0.12meq/L, Cl- -70.67±0.37meq/L. In proteins the concentration of albumin exceeds that of globulin. Albumin- 4.10±0.06meq/L and globulin- 1.87±0.20meq/L. The A/G ratio was 1.67±0.09meq/L and osmolality was 223.80±0.17mOsm. Despite all available information concerning the composition, origin and fate of liquor amnii our knowledge with regard to this fluid remains incomplete. The constitutions of the amniotic fluid are the principal source of information on foetal maturity. Due to differentiation of tissue and ensuing secretary functions no single value or combination of values provide absolute evidence of foetal maturation.